REGROWTH ABILITY OF ARBILA (Phaseolus lunatus L.) AFTER GRASSED AT DIFFERENT DOSAGE OF RHIZOBIUM INOCULANT AND AGE OF PLANT WHEN START GRAZED AT DRY LAND - Bernadete Barek Koten; Redempta Wea; Bambang Hadisutanto; Maria Klara Salli; Agustinus Semang (Buletin Peternakan, 2017)
The study was conducted to evaluate regrowth ability of arbila (Phaseolus lunatus L.) after grazed at different rhizobium inoculants dosage and age of plant to be grassed, have conducted during 6 month at Noelbaki village and Politani Kupang General Laboratory. Factorial design with 3 dose levels of rhizobium inoculants ei: I0 = without inoculant, I10 = 10 g/kg seed dan I20 = 20 g/kg seed) and 3 dose of initial grazing time ei: G20 = 20 days, G30 = 30 days, dan G40 = 40 days, and 3 replications. The variables were number of shoots (shoot, plants vitality (%), covered area (cm), space between crops (crops/ m2), and chlorophyll (mg/ml). Obtained data were tested using analysis of variance followed by Duncan test (Duncan’s new multiple range test / DMRT). Result shows that interaction between inoculant dose with crops’ age when grazed greatly influence the size of covered area (P<0.01), eventhough other variable not influence Duncan test showed, the most extensive covered area are shown by I10G30 (262 cm), I0G40 (126 cm), and I2G40 (123 cm). As single factor, inoculant dose only affect to the size covered area, which the most extensive is shown by I10, and crops’ age when grazed affect the number of shoots, vitality, size of covered area (cm) and space between crops (crops/ m2. It can be concluded, the interaction between inoculum dose  and age of plant to be grassed was affecting the ability of regrowth of arbila, rhizobium inoculum caused arbila to withstand grazing stress, and arbila which is added inoculant 20 g/kg seed and were grazed at age  40 days can regrowth post grazed. It was concluded that the interaction between inoculum dose and age of plant to be grassed was affecting the ability of regrowth of arbila, rizobium inoculum caused arbila to withstand grazing stress, and rhizobium inoculum with dose of 20 g /kg of seed and started grazing at age 40 days which was most able to guarantee the regrowth of plant arbila post-shepherd.